2009
DOI: 10.1016/j.fertnstert.2008.08.074
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for surgically removed fibroids in a large cohort of teachers

Abstract: Objective To describe reproductive and lifestyle correlates of surgically confirmed fibroids. Design Prospective Cohort Study Setting The California Teachers Study (CTS), an ongoing prospective study of over 133,000 female teachers and school administrators identified through the California State Teachers Retirement System. Patients CTS cohort members reporting no prior history of fibroids were ascertained prospectively for surgical diagnosis of fibroids using hospital patient discharge records. Main O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
158
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(172 citation statements)
references
References 36 publications
(53 reference statements)
8
158
5
1
Order By: Relevance
“…Certain studies have shown that the incidence of hysteromyoma varies among populations of different ethnicities (11)(12)(13)(14)(15)(16). For example, the incidence of hysteromyoma in African females is three times as high as that in Caucasian females (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain studies have shown that the incidence of hysteromyoma varies among populations of different ethnicities (11)(12)(13)(14)(15)(16). For example, the incidence of hysteromyoma in African females is three times as high as that in Caucasian females (13).…”
Section: Discussionmentioning
confidence: 99%
“…Also, compared with other ethnicities, African females with hysteromyoma are younger and have larger lesions, with hysteromyomas that grow faster (12,15). The incidence of hysteromyoma in females of African descent is higher than in individuals of other ethnicities, including Hispanic and Asian individuals (11,15,16). Certain studies have indicated that other risks, such as family history, smoking, drinking, hypertension and weight increase, can increase the risk of hysteromyoma, in addition to the risk associated with ethnicity (12,14,16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9,10 Until recently, classification of UL in epidemiologic studies relied on self-reported diagnostic history, medical records, or hospital discharge databases. 3,6,9,[11][12][13] Most studies were restricted to cases with a clinical diagnosis or cases presenting for myomectomy or hysterectomy. Such cases generally represent the symptomatic end of the disease spectrum.…”
mentioning
confidence: 99%
“…For the above reasons, ULs are the most commonly cited indication for hysterectomy (Duhan, 2011). Predisposing factors for UL include environmental and genetic factors, such as early menarche, nullparity, obesity, African-American ethnicity, tamoxifen use (Ross et al, 1986;Samadi et al, 1996;Marshall et al, 1997;Templeman et al, 2009), and polymorphism of the ORC5L, LHFPL3, and PCOLCE genes (Hodge et al, 2009). However, the UL risk associated with programmed cell death 6 (PDCD6) has not been reported.…”
mentioning
confidence: 99%